Folk art Christmas ornaments How to make them - Kenny, Maxine (New York Arco Pub., 1985)
Provides instructions for making colonial, country, Victorian, and international-style Christmas tree ornaments and includes recipes for cookies and candies hung on the tree
55462
Keywords: Christmas Tree; Christmas Ornaments